Nep1-Like Proteins From the Biocontrol Agent Pythium oligandrum Enhance Plant Disease Resistance Independent of Cell Death and Reactive Oxygen Species - Yang, Kun; Chen, Chao; Wang, Yi; Li, Jialu; Dong, Xiaohua; Cheng, Yang; Zhang, Huanxin; Zhai, Ying; Ai, Gan; Song, Qingsong; Wang, Baojian; Liu, Wentao; et al. (Frontiers in Plant Science, 2022)
Microbial necrosis and ethylene-inducing peptide 1 (Nep1)-like proteins (NLPs) act as cytolytic toxins and immunogenic patterns in plants. Our previous work shows that cytolytic NLPs (i.e., PyolNLP5 and PyolNLP7) from the biocontrol agent Pythium oligandrum enhance plant resistance against Phytophthora pathogens by inducing the expression of plant defensins. However, the relevance between PyolNLP-induced necrosis and plant resistance activation is still unclear. Here, we find that the necrosis-inducing activity of PyolNLP5 requires amino acid residues D127 and E129 within the conserved “GHRHDLE” motif. However, PyolNLP5-mediated plant disease resistance is irrelevant to its necrosis-inducing activity and the accumulation of reactive oxygen species (ROS). Furthermore, we reveal the positive role of noncytotoxic PyolNLPs in enhancing plant resistance against Phytophthora pathogens and the fugal pathogen Sclerotinia sclerotiorum. Similarly, noncytotoxic PyolNLPs also activate plant defense in a cell death-independent manner and induce defensin expression. The functions of noncytotoxic PyolNLP13/14 rely on their conserved nlp24-like peptide pattern. Synthetic Pyolnlp24s derived from both cytotoxic and noncytotoxic PyolNLPs can induce plant defensin expression. Unlike classic nlp24, Pyolnlp24s lack the ability of inducing ROS burst in plants with the presence of Arabidopsis nlp24 receptor RLP23. Taken together, our work demonstrates that PyolNLPs enhance plant resistance in an RLP23-independent manner, which requires the conserved nlp24-like peptide pattern but is uncoupled with ROS burst and cell death.